Construction of a parallel computational algorithm based on the Galerkin discontinuous method for solving convective heat transfer problems on unstructured staggered grids - Zhalnin, R. V.; Masyagin, V. F.; Peskova, E. E. (Žurnal Srednevolžskogo matematičeskogo obŝestva (Online), 2018)
The present paper is devoted to the construction of a parallel computational algorithm for solving convective heat transfer problems using the discontinuous Galerkin method on unstructured staggered grids. The computational algorithm is implemented on the basis of MPI parallel computing technology. A special feature of the algorithm is that auxiliary variables that occur when the diffusion terms are approximated by the discontinuous Galerkin method are not involved in interprocessor exchange. The developed parallel algorithm is applied to modelling of temperature dynamics in formation with a vertical injection well and hydraulic fracturing. The paper presents the results of a computational experiment and estimates the effectiveness of a parallel algorithm.